An Unexpected Association in a Patient with Heart Failure Presenting a Surgical Challenge - Alegria, S (2020)
Bicuspid aortic valve (BAV) is the most common form of congenital heart disease and frequently leads to premature valvular dysfunction. BAV is associated with aortic wall abnormalities and a high prevalence of ascending aorta dilatation and coarctation of the aorta (CoA). Consequently, in patients with BAV a careful assessment of the valve, and also of the aortic root and the ascending aorta, should be performed. The most feared complication is aortic dissection, however, the actual incidence of this complication is low. We report the case of a 58-year-old man who presented with New York Heart Association class III heart failure. The work-up revealed BAV with severe stenosis and severe compromise of left ventricle systolic function. In addition, CoA in the isthmus region, and type B dissection of the aorta were diagnosed.